Implicit Meanings of Jentaka Lyrics Song and Video Clip: A Semiotic Analysis - Meiyanti Nurchaerani; Alfian Alfian; Syahiid Hidayatullah R. Hartadhi; Christianto Christianto (UIBU, 2024)
This study analyzed the lyrics and music video of